Evaluation of symptomatic peripheral artery disease with media sclerosis using shear wave elastography of the lower limb muscle. (3rd October 2022) - Maslarska, M; Piepenburg, S; Kaier, K; Freund, G; Bode, C; Hehrlein, C
Abstract: Background: Symptomatic peripheral artery disease (PAD) is challenging to diagnose in the presence of media sclerosis with incompressible arteries since standard ankle-brachial index (ABI) cannot be applied. Shear wave elastography (SWE) provides a novel ultrasound technique to measure muscle stiffness and to visualize muscle deficits at rest and during contraction. Furthermore, reduced muscle stiffness correlates with a possible hypoperfusion in the affected area. It is fast, non-invasive and associated with peripheral muscle weakness in chronic heart failure patients. Purpose: SWE presents an important diagnostic tool for patients with PAD and concomitant media sclerosis. In this prospective observation study we evaluated the alterations of muscle stiffness (measured in kPa) at rest and during controlled activity. Methods: Fifteen patients with peripheral artery disease and media sclerosis were included in this pilot study. Thirteen patients were symptomatic in different stages of PAD as a result of significant arterial stenosis/occlusions of the lower legs as assessed by oscillography and duplex sonography. ABI was invalid due to media sclerosis in all 15 patients. The examination was performed at rest and during contraction depicted by active dorsal flexion of the foot on both sides. The medial gastrocnemius muscle was used as a region of interest. Results: Mean SWE measurements of medial gastrocnemius muscles showed significant muscle weakness at maximum exercise (103.4±25.9 kPa on the asymptomatic vs. 62.5±21.9 kPa in the symptomatic lower leg (p<0.001). Oscillography confirmed the SWE results by a decreased signal on the clinically symptomatic side. Conclusion: SWE is suitable to detect muscle weakness during exercise in the symptomatic leg of mediasclerotic PAD patients. Since ABI measurements are usually invalid these patients with media sclerosis, shear wave elastography of lower limb muscles may contribute for a non-invasive diagnosis of symptomatic PAD. Larger randomized clinical trials are necessary to confirm our results. Funding Acknowledgement: Type of funding sources: None.